2017
DOI: 10.1017/prp.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Confucian Values on Interpersonal Trust, Justice, and Information Sharing of Korean Workers: A Multilevel Analysis

Abstract: T his study examines the effect of supervisors' Confucian values on interpersonal trust, interpersonal justice, and information sharing in the context of South Korean workers, using multilevel analysis. We also investigate the moderating roles of blood, regional, and school ties (BRST) among their relationships. A survey was conducted with 46 supervisors and 210 subordinates from South Korean manufacturing companies. Our empirical findings indicated that supervisors' Confucian values were positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The centrality of followers' and other stakeholders' expectations of principals in defining effectiveness is not a common focus in school leadership and effectiveness research, despite accumulated evidences of its importance in organizational behaviour (Shondrick, Dinh, & Lord, 2010). In this regard, it is important to note the role of societal values on employees' implicit expectations (Yeo, Wildman, & Choi, 2017), which may also shape expectations that vary with context. Further research on this topic is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of followers' and other stakeholders' expectations of principals in defining effectiveness is not a common focus in school leadership and effectiveness research, despite accumulated evidences of its importance in organizational behaviour (Shondrick, Dinh, & Lord, 2010). In this regard, it is important to note the role of societal values on employees' implicit expectations (Yeo, Wildman, & Choi, 2017), which may also shape expectations that vary with context. Further research on this topic is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to athlete-collectivism, athlete-activist could influence other potential athlete-activists (Smith et al, 2016). Various studies (Lim, 2009;Yeo, Wildman & Choi, 2017) found that Confucian harmony has two distinct motives in collectivistic Asian societies: a) appreciation of harmonious relationships (interpersonal trust), and b) harmony as a means to other ends (information sharing framework). For example, the South Korean ice sledge athletes exhibited their interpersonal trust when they collectively participated in the 2018 documentary film 'We ride a sled' aimed to raise awareness on disability rights and Parasport.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, we acknowledged that Chinese are more value-oriented and concerned with social stability, humaneness and righteousness (Yeo et al, 2017). Similarly, Pohl (2002) conducted a comparative study of value preferences indicated that Chinese students emphasized on collectivism compared to Australian students.…”
Section: Confucian Valuesmentioning
confidence: 91%